مقارنة بين أسلوبي الإخفاء في المجالين: الفراغي والترددي للصور الرقميَة - ضاهر, رياض; صالح, إيهاب (Latakia University Journal -Engineering Sciences Series, 2018)
تزداد أهمية أمن المعلومات هذه الأيام بازدياد تعقيد وسائل الاتصال و أنظمة الحواسيب, و على الرغم من الأمان الذي تحققه خوارزميات التشفير للأطراف المتراسلة, تبقى الرسالة المشفرة عرضة لأنواع من الهجمات المختلفة التي قد يكون أحد أهدافها تخريب كمالية المعطيات المتبادلة كتحريفها او إخفاء وجود بعض المعلومات فيها لذا كان من الأفضل إخفاء وجود بيانات سرية يتم تبادلها أصلاً, حتى و إن كانت مشفرة, مما يجعل المهاجم غير قادر على معرفة وجود اتصال سري بين الطرفين المتراسلين من عدم وجوده و عملية الإخفاء هذه لا تنتمي بشكل مباشر إلى علم التشفيرCryptography بل تندرج تحت مسمى علم الإخفاء Steganography .يهدف علم الإخفاء إلى حجب وجود عملية تراسل للمعطيات و هو ما يتطلب وجود وسط مضيف حاملا للرسالة قد يكون أي ملف رقمي سواء كان صورة أو فيديو أو ملفات نصيّة أو اي ملف يمكننا استغلال وجود مساحات غير مستخدمة أو يمكننا استخدامها دون ترك أثر واضح مثير للشبهات على الملف المضيف.يمكن استخدام عدة أساليب تقليدية للقيام بعملية الإحفاء ضمن الأوساط الرقميّة, إلا أن زيادة الاهتمام بمسألة حماية المعلومات و امنها أدى إلى اعتماد عدة خوارزميات متقدمة تعتمد على مفاهيم معالجة الإشارة و نظرية المعلومات و في هذا البحث كان التركيز على خوارزميات الإخفاء الحديثة المستخدمة في الصور الرقمية و التي تعتبر من أكثر الوسائط الرقمية التي تستخدم كوسيط حامل للرسالة السرية, و نقدم دراسة لعملية المقارنة بين أحدث الخوارزميات المتبعة وفق عدد من المعايير الرياضية مع مناقشة النتائج المستخلصة من هذه المقارنة.Nowadays, the importance of information security is increasing according to the complexity of communication devises and their operating systems. Although of the safety that the encryption algorithms can provide between communication users, the encrypted messages may faces lot of attack types, which their purposes vandalism of data integrity such distorting or hiding some or all information, so it will be better to hide information transform existing, even though these information are encrypted, therefore the attacker will not know that there is a secret communication between communication users, this operation of hiding data doesn't belong directly to the Cryptography science, but it falls under Steganography science .In general, Steganography science aim to hide the secret message exchanged between users, which requires a host milieu carrying the secret message, this host may be any file type such as audio file, video file, image file or any type of digital file we can exploit the existence of unused spaces of file, or any space we can use without doing any effect may lead the attackers to know where the message stay in file.It could use some traditional ways to apply data hiding in digital medias, but due to the increment of interest with information safe and security, many advanced algorithms which depend on information theory and signal processing have been adopted, in this paper we concentrated on Steganography algorithms in image files, which considered as the most host files used to carry the secret message, and put a study of comparison process between the newest algorithms that use data hiding in digital images using some mathematical standards, with discuss the final results of this comparison.